Effects of Cobalt and Nickel Substitution on Physical Properties of Perovskite Type Oxides Prepared by the Sol-Gel Citrate Method - Yarbay, R. Z.; Figen, H. E.; Baykara, S. Z. (POLISH ACAD SCIENCES INST PHYSICS, 2012)
In this study, lanthanum and Co-, Ni-based oxides at different compositions were prepared by the sol-gel citrate method. Ammonium carbonate and citric acid were used as complexing agent and solvent. The oxides were characterized by scanning electron microscopy-energy-dispersive spectroscopy, X-ray diffraction, and the Brunauer-Emmett-Teller method. Surface area analysis was carried out and the effects of substitution of cobalt and nickel on the physical properties of the synthesized oxides were investigated.
Keywords: COMBUSTION; OXIDATION; CATALYSTS; STABILITY; PROPANE; Physics